A differential probe design for large-range metal detector. Issue 1 (14th January 2014) - Qiu Xu, Feng; Xu, Xianze; Li, Zhongbing; Le, Yi
Abstract : Purpose: – The metal detector used as a wall scanner has become a kind of popular household instrument. It is important to possess the characteristics, including low-cost, reliability, easy repeatability and simple procedure in this device. The purpose of this paper is to found a model of differential probe applied to metal detector. Design/methodology/approach: – The new model consists of an emitting coil and a differential receiving coil. The emitting coil uses winding inductance to produce a magnetic field and the receiving coil senses the change of magnetic flux. All turns of the receiving coil are designed in the same plane, so it can be fabricated with signal printed circuit board. The balance of differential probe is promised by the constraint relation of the parameters, including the radius and the turns of the receiving coil and the emitting coil. A novel fine adjustment has been proposed to offset the design error that can make the model more ideal. Findings: – The differential probe can be produced easily and need not to be calibrated. In the design, the amplifier and the filter circuit is used for the output signal processing and the harmonic analysis based on Fourier transform is used to analyze the voltage signal in order to detect and distinguish the metallic object. The differential probe in the prototype, which area is π×352 (mm2), can detect the cylindrical metallic object including iron, and aluminum which thickness is 2 mm and radius is 30 mm in the distance of 120 mm. Originality/value: – The model of differential probe proposed in the paper is feasible and effective to apply in the hand-held metal detector.